General Formation of MxCo3−xS4 (M=Ni, Mn, Zn) Hollow Tubular Structures for Hybrid Supercapacitors - Chen, Yu Ming (2017)
A simple and versatile method for general synthesis of uniform one-dimensional (1D) MxCo3−xS4 (M=Ni, Mn, Zn) hollow tubular structures (HTSs), using soft polymeric nanofibers as a template, is described. Fibrous core–shell polymer@M-Co acetate hydroxide precursors with a controllable molar ratio of M/Co are first prepared, followed by a sulfidation process to obtain core–shell polymer@MxCo3−xS4 composite nanofibers. The as-made MxCo3−xS4 HTSs have a high surface area and exhibit exceptional electrochemical performance as electrode materials for hybrid supercapacitors. For example, the MnCo2S4 HTS electrode can deliver specific capacitance of 1094 F g−1 at 10 A g−1, and the cycling stability is remarkable, with only about 6 % loss over 20 000 cycles.